Overview on the principles and methodology in biogeographic zonation research - Thanh, Dang Ngoc (Academia Journal of Biology, 2015)
Based on recent study results of different biogeographers, especially on marine zoogeographic zonation, an overview on the principles and methodology in biogeographic zonation research is given in this paper. A discussion on the widely adopted at present time zonation principles is presented as: Ecological, Taxonomic and Genetic principles, as. well as some actual problems of the biogeographic concepts and methodology such as: biogeographic elements biogeographic structure and biogeographic zonation units scale, a practical method for biogeographic zonation including 4 basic steps is proposed by the author.